THE TIME IS NOW: ABA STANDARD 303(C) AS THE IMPETUS FOR A TRULY INCLUSIVE 1L CLASSROOM - Jennifer Fernandez (Washington University Journal of Law and Policy, 2024)
This fall, law schools were required to implement the American Bar Association’s new Curriculum Standard 303(c), which requires that all law students be educated on bias, cultural competency, and racism. In this Essay, I argue that the American Bar Association’s new Standard is our chance to finally take the steps scholars have advocated for many years and make the law school experience, especially the 1L curriculum, more inclusive. Anything otherwise would be strongly antithetical to the underlying goals of the new standard.
Keywords: ABA; Racism; Bias; 1L; Curriculum